Characterization of the correlated background for a sterile neutrino search using the first dataset of the JSNS $$^2$$ 2 experiment - Y. Hino (European Physical Journal C: Particles and Fields, 2022)
Abstract JSNS $$^2$$ 2 (J-PARC Sterile Neutrino Search at J-PARC Spallation Neutron Source) is an experiment that is searching for sterile neutrinos via the observation of $${\bar{ν }}_{μ } → {\bar{ν }}_{e}$$ ν ¯ μ → ν ¯ e appearance oscillations using muon decay-at-rest neutrinos. Before dedicated data taking in the first-half of 2021, we performed a commissioning run for 10 days in June 2020. Using the data obtained in this commissioning run, in this paper, we present an estimate of the correlated background which imitates the $${\bar{ν }}_{e}$$ ν ¯ e signal in a sterile neutrino search. In addition, in order to demonstrate future prospects of the JSNS $$^2$$ 2 experiment, possible pulse shape discrimination improvements towards reducing cosmic ray induced fast neutron background are described.